Empirical Examination of Career Guidance Activity in the Secondary Socialization in Kindergartens Among the School-age Population - Visztenvelt, Andrea; Galló, Györgyné (Acta Carolus Robertus, 2024)
The aim of our research is to investigate whether knowledge transfer in the field of career guidance can be relevant in the group of school-aged kindergarten students. Based on this, we wanted to explore the relationship between career orientation, school-ready preschoolers and the activities implemented by preschool teachers. The focus of our study was the relationship between the methods of activities performed by kindergarten teachers - which are related to the world of work of adults - and the content and guidelines of career guidance. Through the implementation of structured group sessions, we observed whether career guidance activities could be implemented among school-age preschoolers, and we analyzed the necessity of career guidance activities in preschool education.
Keywords: career guidance; school-ready preschool age group; world of adult work